2015
DOI: 10.1007/s12072-015-9643-z
|View full text |Cite
|
Sign up to set email alerts
|

Performance of transient elastography assessing fibrosis of single hepatitis B virus infection: a systematic review and meta-analysis of a diagnostic test

Abstract: Based on this meta-analysis we claim that liver stiffness measurement using transient elastography has good diagnostic accuracy for predicting single hepatitis B virus-related significant fibrosis and cirrhosis, especially in Asian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
3
18
0
1
Order By: Relevance
“…In two patients, whose fibrosis stage was at a baseline of S3 and S6, respectively, fibrosis regressed to stages S2 and S5 at 24 months of therapy (Table 3). Previous studies (Xu et al, 2015) in Asian cohorts have suggested that TE is a reliable technique for diagnosing liver fibrosis stages. Our results suggest that liver stiffness, although not exclusively representative of liver fibrosis, may also have value as a diagnostic discriminator for patients needing treatment.…”
Section: Longitudinal Evaluationmentioning
confidence: 96%
“…In two patients, whose fibrosis stage was at a baseline of S3 and S6, respectively, fibrosis regressed to stages S2 and S5 at 24 months of therapy (Table 3). Previous studies (Xu et al, 2015) in Asian cohorts have suggested that TE is a reliable technique for diagnosing liver fibrosis stages. Our results suggest that liver stiffness, although not exclusively representative of liver fibrosis, may also have value as a diagnostic discriminator for patients needing treatment.…”
Section: Longitudinal Evaluationmentioning
confidence: 96%
“…Other articles [37][38][39][40][41][42] have confirmed the performance of the method, yielding AUROC values raging between 0.80 and 0.90 (for the prediction of significant fibrosis) and liver stiffness cutoffs varying between 6.6 and 8.8 kPa [9,[43][44][45][46][47]. With regard to the prediction of cirrhosis, AUROCs vary between 0.81 and 0.97 and the cutoffs between 9.4 and 13.4 kPa [44,45].…”
Section: Chronic Hepatitis B (Chb)mentioning
confidence: 74%
“…We chose an LSM cutoff value of 8.0 kPa in our analysis, which was different from previous validation studies (e.g., 7.2‐8.0 kPa for significant fibrosis) . This was because the focus of our current study was to assess the relationship between LSM and various clinical outcomes (e.g., hepatic events, cardiovascular events).…”
Section: Discussionmentioning
confidence: 99%